Microbubble Characterisation for Ballast Water Treatment on Ships over Indonesian Exclusive Economic Zones - Anggun Puspitarini Siswanto (Diponegoro University, 2019)
In generally, the vessel takes on ballast water as it unloads cargo and discharges ballast water as it loads cargo. It is estimated that approximately 7 billion tons of ballast water is transferred globally each year. The total volume of ballast water onboard a ship can be in excess of 5,000 m3. The organisms and pathogens in the water are not necessarily evenly distributed i.e. there may be patches with higher densities. Int his research, we implement micronbubble technology for Ballast Water Treatment. Principally, bubble could be developed in liquid or gas form. The micro term in microbubble reflects to the proportion which is usually in micrometer of its diameter size. Smaller bubble size is expected to give wider surface area as well as affected to greater mass transfer between its surface and interfacial area. Microbubble characterisation was conducted by using high speed camera for bubble size determination. Moreover, a fluidic oscillator was attached into the system to study the efficacy of bubble distribution within ceramic diffuser.